PENYULUHAN ASI EKSKLUSIF DALAM RANGKA MENINGKATKAN PENGETAHUAN IBU DAN PELAKSANAAN ASI EKSKLUSIF DALAM RANGKA MENURUNKAN ANGKA KEJADIAN INFEKSI DAN ANGKA KEMATIAN BAYI DI RUANG BAYI SEHAT RUMAH SAKIT UMUM DAERAH TABANAN - Ni Putu Aniek Mahayani; Sri Utami (JURNAL SEWAKA BHAKTI, 2022)
Breast milk (ASI) is a liquid that comes out of a mother’s breast who has just given birth which is specially created for her baby. Exclusive breast milk (ASI) is breastfeeding the baby for 6 months without any additional fluids except drugs. There are some factors that affect the success of exclusive breastfeeding both internal and external factors of the mother, also influenceable and non-influenceable factors. Mother’s internal factors are nutritional status, education level, and age, as for external factors consist of the influence of the mass media, knowledge of exclusive breastfeeding, and whether there is guidance from health workers. the mother's knowledge factor plays a major role in a success breast-feed. Mothers who have sufficient knowledge about the benefits of breastfeeding will feel more convinced and confident to exclusively breastfeed their babies. This PKM activity aims to increase mother's knowledge about breastfeeding and the benefits of exclusive breastfeeding. The activity begins with socialization to mothers who has given birth, and pregnant women who carry out the pregnancy control to the obstetrics poly, implementation and evaluation of activities in the form of pretest and posttest. From the results of PKM activities, it is found that there are 85% increase of mother's knowledge about breastfeeding and the benefits of exclusive breastfeeding. The activity outcome of exclusive breastfeeding is 60% after 6 months evaluation.